KOMPETENSI GURU MENURUT ABU HAMID AL-GHAZALI: RELEVANSINYA DENGAN PENDIDIKAN DI ERA MODERN - rois luthfi; Sigit Purnama (IAIN Pontianak, 2022)
This study aims to explore teacher competence according to Al-Ghazali's view and relate it to modern education. This research is an analytical study of teacher competence according to Al-Ghazali which is in the book Ihya' 'Ulum al-Din about educators. Among the teacher's competencies according to Al-Ghazali is having a sense of affection for their students. In the modern era like now, this competency is expected to be possessed by teachers. This hope, at least, arises because of cases of violence and sexual harassment perpetrated by teachers against their students. The teacher, who should be a role model, actually acts and acts immorally. This is a very worrying fact. Al-Ghazali, one of the famous Muslim figures with his title as hujjatul Islam, has contributed several thoughts related to educator competence. His thoughts are certainly very interesting to be studied in more depth. In more detail, the competencies suggested by Al-Ghazali to be possessed by an educator, will be explained in this article.